REDUCING THE ROLE CONFLICT OF WORKING WOMAN: BETWEEN WORK AND FAMILY CENTRALITY - Ranihusna, Desty; Wulansari, Nury Ariani (Jurnal Dinamika Manajemen, 2015)
The aim of this study is to find direct impact of pay satisfaction in WFC and examines direct impact of WFC and FWC for work satisfaction. It also examines impact of moderating variable of work-family centrality moderating variable) from relation of WFC and FWC in work satisfaction (case study of married female lecturers in UNNES). This research was done because there were differences between results of WFC and FWC to JS and recommendation to add moderating variable and PS to WFC. It used SPSS to examine hypothesis with CFA, to test validity, classical assumption testing and t test was also used. Moderating variable was tested by value of absolute deviation. The data in this research is primary data in the form of questionnaire and interview. Â The result shows that there are strong impacts between PS and WFC. There is no impact between WFC and FWC to JS. Supporting moderating variable is Work Centrality. Although, they prioritize their family, female lecturers are still trying to work professionally